2023
DOI: 10.14233/ajchem.2023.26931
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Polarity in Binary Liquid Mixtures as a Function of Volume Fraction

Abstract: The variation of solvatochromic polarity parameters as a function of mole fraction data may not represent the realistic environment of the solvatochromic probe molecule. This is because of the fact that the solvation environment of the solvatochromic probe molecules is not only determined by the number of individual solvent molecules around it but also by the size of those individual solvent molecules. In this regard we wish to understand the variation of ET N polarity parameter of binary liquid mixtures as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 56 publications
1
2
0
Order By: Relevance
“…We are therefore in full agreement with the conclusions of [133], that the volume fraction gives better results in terms of linear correlation. For the correlation with E T (30), however, it makes no qualitative difference whether the mass or the volume fraction is used to determine N av,z .…”
Section: 2-ethanediol/water Methanol/water and Ethanol/water Mixturessupporting
confidence: 91%
See 2 more Smart Citations
“…We are therefore in full agreement with the conclusions of [133], that the volume fraction gives better results in terms of linear correlation. For the correlation with E T (30), however, it makes no qualitative difference whether the mass or the volume fraction is used to determine N av,z .…”
Section: 2-ethanediol/water Methanol/water and Ethanol/water Mixturessupporting
confidence: 91%
“…Bentley [27] has shown that the volume fraction correlates better linearly with the static dielectric constant (ε r ) or the E T (30) values of alcohol/water mixtures than the mole fraction as a composition parameter of alcohol/water mixtures. The volume fraction has also been recommended in a recent publication to explain the E T (30) as a function of solvent composition more accurately than using the mole fraction [133]. Accordingly, for ethanol/water and methanol/water mixtures, the N av,w and N av,v quantities have been calculated and empirically tested as variables for correlation with E T (30) [62].…”
Section: 2-ethanediol/water Methanol/water and Ethanol/water Mixturesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the analysis of solvatochromic data, the mole or volume fractions of mixtures are still mainly used as measures of the composition of mixtures. [14][15][16][17] The eqn. (6) gives the average molar concentration of the mixture in terms of a specific fraction z of the mixture.…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore clear that it is of fundamental importance, since the choice of the measure of the quantitative composition of the mixture can lead to a different physical statement. [14][15][16][17] This important fundamental problem has been circumvented by many authors by using the quantity that best correlates with the model used in an appropriate relationship. Thus, in the past, the discrepancies were ignored and the mole fraction was used as a seemingly logical compromise because it is linear to the Gibbs free energy of mixing.…”
Section: Introductionmentioning
confidence: 99%